Peculiarities of clay soils research in the course of forensic soil examination - V. M. Shevchenko (Bulletin of Kharkiv National University of Internal Affairs)
Methods of clay soils research that take into account the specifics of expert study of soil objects are defined. In order to classify a soil as clay, the mechanical composition is first examined. According to this indicator, clay soils are divided into loam, light clay, and heavy clay. Clay is classified as a mineral resource of national importance, while loam is classified as a mineral resource of local importance. These soils may be subject to illegal mining. The article analyses the possibilities of applying various methods for the expert study of clay soils, namely, the method of sedimentation analysis and the ‘field’ method. After establishing the mechanical composition and classification of samples as clay soils, it is recommended to determine the plasticity index, according to which the soils are classified as loams or clays. The analysis is described in accordance with the State Standard of Ukraine Б B.2.1-17:2009 “Bases and foundations of buildings and structures. Soils. Methods of laboratory determination of physical properties”.